Assertion of Ethnical Identity through Sonia Sanchez's " This is Not a Small Voice" - Rubaya Jabbar Ibrahiml; Susan Raheem Rahman JaF (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The poem "This Is Not a Small Voice" by Sonia Sanchez is a moving examination of how ethnic identity is asserted within the American community. Sanchez captures the voice and experiences of African Americans collectively through vivid imagery and evocative language, highlighting the importance of group membership in forming both individual and collective identity. This analysis explores how Sanchez's poem serves as an example of the processes of self-enhancement and uncertainty reduction within the context of ethnic identity, drawing on social identity theory's emphasis on self-categorization and intergroup dynamics. By emphasizing their beauty, skill, aspirations, joy, and love, the poem goes beyond the common narrative of trauma and oppression, highlighting the diverse and multifaceted aspects of their identity. Further, the poem shows how people can assert their ethnic identity to combat harmful stereotypes and promote a sense of belonging by celebrating the strength and love of the African American community. It also provides insights into the varied ways in which ethnic identity is affirmed and communicated. The investigation offers a powerful message of solidarity and pride, reinforcing the idea that every voice within the community contributes to its strength and effect